Analysis of D+->K-S((0))K+ and D+->K-S((0))pi(+) - Bishai, M; Fast, J; Gerndt, E; Hinson, J; Menon, N; Miller, D; Shibata, E; Shipsey, I; Yurko, M; Gibbons, L; Johnson, S; Kwon, Y; et al. (1997)
Using data collected with the CLEO II detector at the Cornell Electron Storage Ring, we present new measurements of the branching fractions for D+ → KS 0K+ and D+ → KS 0π+. These results are combined with other CLEO measurements to extract the ratios of isospin amplitudes and phase shifts for D → KK and D → Kπ.